2017
DOI: 10.1139/cjps-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean and winter wheat herbicides on oilseed radish establishment and growth

Abstract: Residual herbicides can cause injury to a future crop. Residual herbicides applied to soybean [Glycine max (L.) Merr.] or winter wheat (Triticum aestivum L.) may impact cover crops seeded in the same growing season. The objective of this study was to determine the effect of residual herbicides on oilseed radish (Raphanus sativus L.) establishment and growth after 10 postemergence (POST) broadleaf herbicides were applied in winter wheat and 12 preemergence (PRE) and 7 POST herbicides were applied in soybean. Oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Previous trials using flumetsulam showed significant reductions in wild radish seed production (>75%) across nine locations when applied at the flowering stage of growth (Madafigilio et al 2006). Other studies found significant reductions in biomass of related oilseed radish (Raphanus sativus L.) planted after flumetsulam and imazethapyr use in corn or soybean (Brooker et al 2020;Cholette et al 2017;Cornelius and Bradley 2017) due to herbicide persistence in the soil. Our experiment evaluated 2,4-D, flumetsulam, and imazethapyr at lower use rates than would be applied in corn and soybean in the aforementioned studies.…”
Section: Weed Controlmentioning
confidence: 99%
“…Previous trials using flumetsulam showed significant reductions in wild radish seed production (>75%) across nine locations when applied at the flowering stage of growth (Madafigilio et al 2006). Other studies found significant reductions in biomass of related oilseed radish (Raphanus sativus L.) planted after flumetsulam and imazethapyr use in corn or soybean (Brooker et al 2020;Cholette et al 2017;Cornelius and Bradley 2017) due to herbicide persistence in the soil. Our experiment evaluated 2,4-D, flumetsulam, and imazethapyr at lower use rates than would be applied in corn and soybean in the aforementioned studies.…”
Section: Weed Controlmentioning
confidence: 99%